A Computer-Aided Approach to Equilibrium Design Based on Graphic Statics and Combinatorial Variations. (April 2020) - Ohlbrock, Patrick Ole; D'Acunto, Pierluigi
Abstract: This article introduces a series of significant enhancements to the Combinatorial Equilibrium Modelling (CEM), a computer-aided form-finding approach to generate and control three-dimensional structures in static equilibrium based on topological considerations. In comparison to the initial formulation of the CEM, this article presents several procedures that extend the applicability of the CEM to several structural topologies and load cases, while allowing the designer to engage with different types of constraint-based optimisation problems. As described in the article, these new features of the CEM have been implemented in a digital tool for form-finding, which has been applied to a series of design examples and case studies to demonstrate the usability of the proposed approach for conceptual structural design. Graphical abstract: Highlights: Extension of the Combinatorial Equilibrium Modelling (CEM). Possibility to deal with form-dependent load cases and non-planar topologies. Introduction of procedures to address constraint-based design problems. Introduction of load-path optimisation using vector-based 3D graphic statics. Implementation of a unified computer-aided CEM toolkit. Application of the proposed methodology to actual structural design problems.